1970
DOI: 10.1007/bf02642003
|View full text |Cite
|
Sign up to set email alerts
|

The martensite phases in 304 stainless steel

Abstract: A detailed analysis of martensite transformations in 18/8 (3b4) stainless steel,.utilizing transmission electron microscopy and diffraction in conjunction with X-ray and magnetization techniques, has established that the sequence of transformation is y ~ E ~ a. E is a thermodynamically stable hcp phase whose formation is greatly enhanced as a result of plastic deformation. Comparison with the E ~a transformation in pure Fe-Mn alloys lends further support to the above sequence and suggests that a transforma-.ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
165
1
10

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(204 citation statements)
references
References 13 publications
9
165
1
10
Order By: Relevance
“…292 Significant discrepancy still exists in explaining the 293 strengthening mechanisms of metastable austenitic stain-294 less steels and, in concrete, the effect of the strain-in-295 duced a¢-martensite phase. Since the highly dislocated 296 a¢-phase is much harder than the austenite, some 297 authors [40,41] consider austenite-martensite mixtures as 298 composites of soft austenitic matrix with hard martensite 299 dispersion. Spencer et al [42] demonstrated that marten-300 site sustains a clearly higher stress than austenite, 301 concluding that a¢-martensite acts as the reinforcing 302 phase.…”
mentioning
confidence: 99%
“…292 Significant discrepancy still exists in explaining the 293 strengthening mechanisms of metastable austenitic stain-294 less steels and, in concrete, the effect of the strain-in-295 duced a¢-martensite phase. Since the highly dislocated 296 a¢-phase is much harder than the austenite, some 297 authors [40,41] consider austenite-martensite mixtures as 298 composites of soft austenitic matrix with hard martensite 299 dispersion. Spencer et al [42] demonstrated that marten-300 site sustains a clearly higher stress than austenite, 301 concluding that a¢-martensite acts as the reinforcing 302 phase.…”
mentioning
confidence: 99%
“…This is attributable to an increased rate of martensite formation in conjunction with a mechanical effect of this martensite tenned the "window mechanism" (l6). Bee martensite is frequendy observed at intersections of two shear bands in 18-8 stainless steel (16)(17)(18)(19). It has been previously noted that the bee structure can be constructed from the fcc structure by two independent shears (20), for example at the intersection of an hcp shear band with a second shear band of highly faulted fcc or hcp crystal (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that ε-martensite is formed at low strains in some low-SFE metastable steels, such as AISI 304 and 316 [15][16] . Generally, reaction (4) takes place for metastable austenitic steels with SFE < 20 mJ/m 2 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Many authors studied the deformation induced martensites in austenitic [15][16][17][18][19][20][21][22] , duplex and lean duplex stainless steels [23][24] . Both ε-and α'-martensites can be observed by transmission electron microcopy (TEM) and quantified by X-ray diffraction (XRD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation